The Mediation of Self Efficacy among Career Commitment and Subjective Career Success - Permata Uswita, Indah; Trinanda, Okki (Human Resource Management Studies, 2024)
This study uses Self Efficacy as a mediator to look at the relationship between Career Commitment and Subjective Career Success in civil servants (PNS) Badan Pusat Statistik Kabupaten Lima Puluh Kota. This study employs quantitative methods and is classified as causal research. The respondents for this research were 32 respondents using the total sample technique. Data was gathered using a questionnaire featuring a Likert scale. Data analysis techniques use SEM with the SmartPLS4 application. From the research results, it was found that Career Commitment and Self-Efficacy positively and significantly impacts Subjective Career Success. Apart from that, this research also proves that Self Efficacy mediates the impact of Career Commitment on Subjective Career Success positively and significantly.